PENGARUH SOLVABILITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM PERUSAHAAN MAKANAN DAN MINUMAN TERDAFTAR DI BEI PRIODE 2018-2020 - Hartini Hartini; Rani Wajriani (Universitas Hamzanwadi, 2022)
The study aims to test the effect of Debt to Equity Ratio and Return On Equity on the share prices of food and beverage companies that distribute dividends and are listed on the IDX in 2018-2020. The population in this study were all food and beverage companies that distributed dividends and registered with the IDX priode 2018-2020. The sample is done with census techniques. The samples used were 10 food and beverage companies.The data analysis technique used is the analysis of panel data analysis with the help of the eviwes 09 application. The results of analysis and discussion of this study showed (H1) Partially DER has a significant negative effect on stock prices and (H2) Partially ROE has a significant positive effect on stock prices. The results of the coefficient of determination (R2) test showed that the value of Adjusted R Square = 0.317237 this means the ability of DER and ROE in explaining stock prices in food and beverage companies that distributed dividends in 2018-2020 amounted to 31.72% the remaining 68.28% was influenced by other factors outside the model not studied in the study.